2019
DOI: 10.1177/0016986219886933
|View full text |Cite
|
Sign up to set email alerts
|

Supports for Youth in Accelerated High School Curricula: An Initial Study of Applicability and Acceptability of a Motivational Interviewing Intervention

Abstract: High school students in accelerated classes face heightened school-related stressors but have access to few specialized supports. This article describes the development and initial application of the Motivation, Assessment, and Planning (MAP) intervention, developed to meet the needs of freshmen in Advanced Placement (AP) and International Baccalaureate (IB) curricula. MAP is grounded in motivational interviewing and designed to evoke behavior change following one to two individual meetings with a coach. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…At the start of the intervention, participants were asked to complete a short demographics questionnaire (see Figure 2). The first meeting used a protocol, designed by the first author and modified from O'Brennan et al . (2020), intending to provide a framework for fidelity of implementation and the quality of MI utilized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the start of the intervention, participants were asked to complete a short demographics questionnaire (see Figure 2). The first meeting used a protocol, designed by the first author and modified from O'Brennan et al . (2020), intending to provide a framework for fidelity of implementation and the quality of MI utilized.…”
Section: Methodsmentioning
confidence: 99%
“…Participant satisfaction surveys and open-ended questions drew from publications resulting from an IES grant (R305A150543; O'Brennan et al ., 2020; Shum, 2020). Psychometric properties are provided in the technical manual associated with O'Brennan et al . (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Five teachers sought student participation and parent permission from all ninth-grade students enrolled in a state-approved Pre-IBD course, Inquiry Skills (School C), or AP Human Geography (School D). We invited students who returned signed parent consent forms to take part in the portions of the larger study that involved collection of personal and confidential data (e.g., assessment of student mental health and academic outcomes across time, as analyzed in studies reported elsewhere [O’Brennan et al, 2020; Parker et al, 2019; Suldo et al, 2019]) while all students in the classrooms where ACE was implemented were invited to provide anonymous feedback on their perceptions of the curriculum. A total of 331 ninth-grade students agreed to participate in the larger study (participation rate = 93.0%; 3.6% of parents declined consent; 3.4% of students did not return parent consent forms).…”
Section: Methodsmentioning
confidence: 99%
“…MTSS approaches involve preventative (Tier 1), early intervention (Tier 2), and later intervention (Tier 3) strategies to address non-problematic, acute, and chronic issues, in this case to improve school attendance and to ameliorate emerging and intense school attendance problems (August et al, 2018). MTSS approaches also contain several spectra with respect to nuanced and tailored responses that are administered across various settings and providers (O'Brennan et al, 2020). MTSS approaches remain in the nascent stage with respect to SA/Ps, though recommendations for each level have been developed Chang et al, 2018).…”
Section: Postmodern Dimensionsmentioning
confidence: 99%